Adaptation - Base of Protection of Plant Organism from the Influence of Heavy Metals - Dovgopolа Kateryna; Garkava, Kateryna; Bruzgina, Tetyana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The study of the adaptation of medicinal plants in the area near the aerodrome to determine the degree of penetration of soil to heavy metals was a purpose of our investigations. It was established of level of biological resistance of plants to pollution for environmental monitoring of the environment. The soil samples and medicinal plants were collected on the territory adjacent to the Zhulyany airfield in the Kyiv region and the aerodrome in Nizhyn, Chernihiv region. To study, the roots of Taraxacum officinale W. and Cichorium intybus L. have been isolated. These parts of plants are used in official medicine for phytopreparations, therefore analysis of the content of heavy metals in them is relevant. In the soil, the content of heavy metals (Cd, Zn, Pb, Cu) was determined using HCl (1 N), in plants – HNO3 (1 : 1) by atomic absorption spectrophotometer C-115. To estimate soil contamination, the coefficient of the technogenic concentration was used. The coefficient of biological absorption is used to determine the intensity of migration of heavy metals from the soil to plants. The analysis of the lipid composition in medicinal plant samples was carried out by gas-liquid chromatography. It is established that in soil the content of heavy metals doesn’t exceed the maximum permissible concentrations. Heavy metals according to the intensity of accumulation by plants have the following order: Cd > Cu > Zn > Pb. The property of the investigated plants for the accumulation of heavy metals can be used as one of the methods of phytoremediation and phytomonitoring of the medium. Investigation of the content of fatty acids in the plant material may indicate the reaction of the plant organism to stress and as a consequence of further study of the process of adaptation of the plant to the state of growth. The conditions of germination have an effect on the biochemical parameters of biologically active substances in Taraxacum officinale and Cichorium intybus. It has been established that Cichorium intybus is more resistant to unfavorable conditions of germination.